2010
DOI: 10.1021/jf9045304
|View full text |Cite
|
Sign up to set email alerts
|

Value-Added Processing of Peanut Meal: Aflatoxin Sequestration during Protein Extraction

Abstract: The efficacy of a bentonite clay, Astra-Ben 20A (AB20A), to sequester aflatoxin from contaminated (approximately 110 ppb) peanut meal during protein extraction was studied. Aqueous peanut meal dispersions (10% w/w) were prepared by varying the pH, temperature, enzymatic hydrolysis conditions, and concentrations of AB20A. After extraction, dispersions were centrifuged and filtered to separate both the water-soluble and the water-insoluble fractions for subsequent testing. Inclusion of AB20A at 0.2 and 2% reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 33 publications
1
15
0
1
Order By: Relevance
“…From infrared spectroscopy, Deng et al (2010) concluded that hydrogen bonds between AfB1 carbonyl groups and the hydration water of exchangeable cations in clays is the dominant bonding force under humid conditions. Aflatoxin adsorption from aqueous corn and peanut meal to feed additives was consistent with animal feeding studies that used the feed additives, Novasil, Novasil Plus, Astra-Ben 20, Astra-Ben 20A, sepiolite, and activated (Norit-A) carbon (Jaynes et al, 2007;Seifert et al, 2010). Feed additives that effectively reduced or prevented aflatoxin toxicity in feeding studies adsorbed more AfB1 from aqueous corn and peanut meal.…”
supporting
confidence: 73%
“…From infrared spectroscopy, Deng et al (2010) concluded that hydrogen bonds between AfB1 carbonyl groups and the hydration water of exchangeable cations in clays is the dominant bonding force under humid conditions. Aflatoxin adsorption from aqueous corn and peanut meal to feed additives was consistent with animal feeding studies that used the feed additives, Novasil, Novasil Plus, Astra-Ben 20, Astra-Ben 20A, sepiolite, and activated (Norit-A) carbon (Jaynes et al, 2007;Seifert et al, 2010). Feed additives that effectively reduced or prevented aflatoxin toxicity in feeding studies adsorbed more AfB1 from aqueous corn and peanut meal.…”
supporting
confidence: 73%
“…Infrared spectroscopic examination of AfB1-smectite complexes suggests that hydrogen bonds between AfB1 carbonyl groups and the hydration water of exchangeable cations in clays is the dominant bonding force under humid conditions [16]. Aflatoxin adsorption from aqueous corn and peanut meal to feed additives was consistent with animal feeding studies that used the feed additives Novasil Plus, Astra Ben 20A, sepiolite, and activated (Norit-A) carbon [17,18]. Feed additives that effectively reduced or prevented aflatoxin toxicity in feeding studies adsorbed more AfB1 from aqueous corn and peanut meal than feed additives that did not prevent toxicity.…”
Section: Introductionmentioning
confidence: 77%
“…The effectiveness of a commercially available bentonite clay, sold under the trade name Astra-Ben 20A (AB20A), to sequester aflatoxin was evaluated during protein extraction of contaminated peanut meal [60]. In the proposed method, aqueous peanut meal dispersions (10%, w/w) were prepared by varying the pH, temperature, enzymatic hydrolysis conditions, and concentrations of AB20A.…”
Section: Aflatoxin Decontaminationmentioning
confidence: 99%